Aging in a Digital World - Quinn, Kelly; Massanari, Adrienne; Birkland, Johanna; Comunello, Francesca; Rosales, Andrea; Mulargia, Simone; Fernández-Ardèvol, Mireia; Quan-Haase, Anabel (AoIR Selected Papers of Internet Research, 2016)
The temporality of digital living is typically associated with the short history of the internet, the rapid obsolescence of digital technologies, and even the compression of time and space afforded through internet communication. We often overlook, however, the temporality of those that engage with digital life, assuming instead that everyone has citizenship in our digital world. Digital existence, however, appears to be somewhat attached to age and aging. And despite that today’s older adults are healthier and better educated than prior generations, many of those over the age of 50 are somewhat isolated from digital life. Older adults have been slower to use the internet, are less likely to have broadband access, and adopt technologies such as social media and smartwatches at lower rates. Increasingly, though, they are using new technologies and putting them to use in different ways and for different purposes than younger adults. For example, though they lag younger populations in adoption of smartphones and Twitter, the proportion of those owning tablets and e-readers compares much more favorably (Smith, 2014). Physical, perceptual and cognitive changes coincident with aging may present some explanation for this lower engagement, yet we suspect something more. There is mounting evidence that older adults approach digital life from unique perspectives. Older adults are often challenged by having to navigate unfamiliar concepts and interfaces, challenges often associated with a lack in digital literacy skills. But viewed through the lens of life experience, older adults bring perspectives to their use of technology that are distinct from those of younger users. Who are these emerging entrants to digital life? What challenges and opportunities are associated with digital living in later life? What does it mean to grow older in the digital or to digitally age? This panel will explore the intersection of the internet and later life stages to begin to give shape to some answers. Our first panelist begins with an exploration of the spectrum of digital technology use at older ages. Using an interpretive interactionist approach, this study examines the ways in which older adults are introduced to, use, display, and assign meaning to digital technologies. A typology of users emerges, revealing technology adoption at older ages to be a complex and dynamic process. One of the challenges to digital living in later life is that the training and education life stage, which typically takes place in takes place during youth and young adulthood, has passed. Our second panelist examines the challenges inherent in acquiring digital literacy at older ages. Using a mixed methods approach, this study highlights that attaining digital competency at older ages not only encompasses the acquisition of skills, but also must focus on the cognitive and socio-emotional aspects of digital engagement to be truly successful. Our third paper will focus on the adoption of a specific digital technology by older adults, a smart watch, and draws attention to the domestication processes that older adults employ in the adoption of a digital device. Using interviews, focus groups, and user logs, this study explores the discourses around the user relationship with the smartwatch, as well as its tracked use/non-use. In doing so, we are provided with a nuanced view of how technology use intersects with personal values and identity at older ages. Media, especially mass media, are powerful forces of socialization in our culture. The ways in which groups are presented within media, often reflect a particular societal vision and create a social reality by suggesting ways in which the group in question ‘should’ act. Our fourth paper explores the role of digital play in older adulthood by examining the media representation of older adults as video game players. Through a content analysis of major newspaper and news organization accounts, this study explores how media representations resist and reinforce prevailing positive and negative stereotypes of older adults and aging, and discusses the implications. Finally, our fifth panelist contemplates what it means not only to age in a digital world, but also what it means to age in an era that at once experiences rapid digital obsolescence while simultaneously considering the internet’s potential immortality. By highlighting the intrinsic tension between the rhetoric of computer-mediated communication and the ways in which aging users conceive of and participate in internet communication, this study exposes how internet rules impact contemporary online and offline social interaction, and by extension, the digital reality of older adults. In sum, this collection of papers provides a varied and nuanced view of what it means to age and be aging in today’s digital world. Taken together, they provide important perspectives on how later life stages overlap with the internet, especially as its use grows increasingly central to the provision of information, resources, and sociality. References Smith, A. (2014). _Older Adults and Technology Use_. Washington, DC: Pew Research. Retrieved from http://www.pewinternet.org/2014/04/03/older-adults-and-technology-use/